Peran Keluarga dan Pola Makan Balita Stunting - Pipit Festi Wiliyanarti; Israfil .; Ruliati . (Jurnal Keperawatan Muhammadiyah, 2020)
Role of family is behavior which is expected by family relate to status or domicile individual in family. While eating pattern or food pattern is the way of someone or a group of people exploit to eat available as reaction of economic pressure and social-culture happened.Â  Food pattern has relation with food habit. Food pattern can change that is suitable with growth of industrialization and economics.This Research design used analytic method with approach of Cross Sectional. Method of Sampling was used by Simple Random Sampling. The Independent variable was role of family and dependent variable was food pattern. Research of data was taken by using questioner. After data of questioner gathered tabulation later; then and in test by using test of Spearman Rank with the level of meaning Î± = 0, 05.Â Result of research of responder that is most role of good family counted 20 respondents (61%), and most of food pattern for baby aged 5 years was good counted 22 respondents (67%). From result of statistical analysis with test of Spearman Rank u in getting value Ï =0,014 < Î± =0, 05. Role of family that influenced on food pattern for baby aged 5 years. IfÂ  role of family is good, food pattern will be looked better, on the contrary ifÂ  role of family, less foodÂ  pattern will be bad so that frequency, quality , quantities is not maximal.